Late-onset efavirenz toxicity: A descriptive study from Pretoria, South Africa - Lyneshree Munsami; Clara M. Schutte; Maryke de Villiers; Juliane Hiesgen (AOSIS, 2023)
Background: The neuropsychiatric side effects of efavirenz occur mainly early during treatment and are usually mild. A lesser-known and serious complication is late-onset efavirenz toxicity causing ataxia and encephalopathy. Data regarding this condition are limited. Objectives: We describe the clinical picture of late-onset efavirenz toxicity, investigate co-morbidities and report outcomes. Method: This descriptive study of all patients with late-onset efavirenz toxicity was conducted over three years at Kalafong Provincial Tertiary Hospital, Pretoria, South Africa. Results: Forty consecutive patients were identified. Mean age was 42.1 years, three patients (7.5%) were male and the mean efavirenz level was 49.0 µg/mL (standard deviation [s.d.]: 24.8). Cerebellar ataxia (82.5%) and encephalopathy (47.5%) were the most common presenting features (40.0% had both); four patients presented with psychosis. Presence of encephalopathy and/or cerebellar ataxia was associated with higher efavirenz levels compared with psychosis (52.1 µg/mL, s.d.: 24.1 vs 25.0 µg/mL, s.d.: 17.1). In most patients, symptoms resolved, but four patients (10.0%) died, and one patient remained ataxic. Conclusion: Late-onset efavirenz toxicity typically presented with ataxia and encephalopathy, but psychosis can be the presenting feature. The outcome after withdrawal was good, but the mortality of 10.0% is concerning. Recent changes in guidelines favour dolutegravir, but many patients remain on efavirenz, and awareness of the condition is vital. What this study adds: This large, single-centre study contributes to the limited data of HIV-positive patients with late-onset efavirenz toxicity and emphasises its ongoing relevance in clinical practice.